2008
DOI: 10.1093/toxsci/kfn148
|View full text |Cite
|
Sign up to set email alerts
|

Do Parabens Have the Ability to Interfere with Steroidogenesis?

Abstract: The effects of ethyl and butyl paraben on steroidogenesis were evaluated in rats exposed in utero. Pregnant Wistar rats were dosed from gestational day (GD) 7 to GD 21, followed by examination of the dams, and the fetuses. Additionally, both parabens were tested in vitro in the H295R steroidogenesis assay and in the T-screen assay, the later to test for their ability to act as thyroid hormone receptor agonist or antagonist. In the in utero exposure toxicity study, neither ethyl nor butyl paraben showed any tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
75
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 132 publications
(81 citation statements)
references
References 25 publications
5
75
0
1
Order By: Relevance
“…Some parabens have been shown to have weak estrogenic effects in vitro and in animal studies (Okubo et al, 2001;Byford et al, 2002;Darbre et al, 2002Darbre et al, , 2003Darbre et al, , 2004Lemini et al, 2003;Pugazhendhi et al, 2005). Furthermore, studies have shown effects on the male reproductive system, resulting in the reduction of testosterone levels and mature sperm counts, in rats and mice after in utero exposure to some parabens (Oishi, 2001(Oishi, , 2002(Oishi, , 2004Kang et al, 2002), whereas other studies could not confirm these effects (Hoberman et al, 2008;Taxvig et al, 2008). Recently it has been discussed whether parabens could have an adverse effect on the testis mitochondria function, followed by a decreased reproductive potential (Tavares et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Some parabens have been shown to have weak estrogenic effects in vitro and in animal studies (Okubo et al, 2001;Byford et al, 2002;Darbre et al, 2002Darbre et al, , 2003Darbre et al, , 2004Lemini et al, 2003;Pugazhendhi et al, 2005). Furthermore, studies have shown effects on the male reproductive system, resulting in the reduction of testosterone levels and mature sperm counts, in rats and mice after in utero exposure to some parabens (Oishi, 2001(Oishi, , 2002(Oishi, , 2004Kang et al, 2002), whereas other studies could not confirm these effects (Hoberman et al, 2008;Taxvig et al, 2008). Recently it has been discussed whether parabens could have an adverse effect on the testis mitochondria function, followed by a decreased reproductive potential (Tavares et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, investigation of the effects of exposure to parabens during gestation to lactation is important because exposure to estrogenic chemicals during development could be a contributory factor in the rising incidence of endocrine dysfunction of offspring later in life [3,5,14,16,26]. But, the effects of early exposure to parabens are not consistent in previous reports [6,13,27,28]. Furthermore, the effects of early exposure to parabens on the endocrine system in adult female offspring, except for vaginal opening and intact uterus weight [13], are unclear.…”
mentioning
confidence: 86%
“…They have been detected in human urine collected from a demographically diverse group of male and female adults with no known exposure to parabens, suggesting that the majority of people have already been exposed to them [32]. Several studies indicate that exposure to parabens modulates the endocrine system and thus may have harmful consequences on animal and human health [4,7,13,22,28] because of the estrogenic activities of these compounds in vitro and in vivo [7,24], and anti-estrogenic activity in human skin has been shown [22]. In addition, exposure to parabens during adult periods has been implicated in reduction of the male reproductive system in rodents [7,19,20,21], whereas a recent study could not confirm these effects [10].…”
mentioning
confidence: 99%
“…The A-screen is an androgen-responsive CPA based on the MCF-7 cell line transfected with the human-androgen receptor [62]. The T-screen is another CPA used to detect binding and activation of the thyroid receptor (TR), thereby determining the ability of a compound to be a thyroid hormone receptor agonist or antagonist [20,[63][64][65]. These assays are limited in that only effects related to binding can be detected but not effects linked to the disturbance of hormone-synthesis pathways or hormone transport.…”
Section: Yeast Cell-line Rgasmentioning
confidence: 99%
“…A mixture of all tested phytoestrogens (PEs) increased 17b-E2 production and decreased testosterone production, indicating increased aromatase activity [25]. In addition, it has been used to study androgenic effects of a mixture of three azole fungicides [11], and endocrine-disrupting effects of nitrate and nitrite [20] and parabens [63].…”
Section: Endocrine Disruption At Hormone-production Levelmentioning
confidence: 99%